24th Digital Avionics Systems Conference
DOI: 10.1109/dasc.2005.1563325
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Merging and Spacing Operations with Continuous Descent Approaches

Abstract: Researchers at the NASA Langley ResearchCenter are developing the Airborne Precision Spacing (APS) concept to increase runway arrival throughput at capacity-constrained airports. Under APS operations, arrival capacity is increased by improving the precision of inter-arrival spacing at the runway threshold. Flight crews achieve this improved precision with the assistance of a new flight-deck system, which allows spacing operations to commence even while the aircraft and its lead are on different arrival routes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Initial results of this experiment show high correlation with past Langley experiments. 17,18,19 Figure 5 shows the behavior of the 26 th and 27 th aircraft in the middle of a 40 aircraft arrival stream merging in a nominal scenario. The momentary increase in airspeed at Top of Descent at the TRACON boundary (FL110) is due to the difference between ASTAR algorithm calculations and the aircraft's Flight Management System calculations.…”
Section: Experiments Results For Flight Crew Merging and Spacing Amentioning
confidence: 99%
“…Initial results of this experiment show high correlation with past Langley experiments. 17,18,19 Figure 5 shows the behavior of the 26 th and 27 th aircraft in the middle of a 40 aircraft arrival stream merging in a nominal scenario. The momentary increase in airspeed at Top of Descent at the TRACON boundary (FL110) is due to the difference between ASTAR algorithm calculations and the aircraft's Flight Management System calculations.…”
Section: Experiments Results For Flight Crew Merging and Spacing Amentioning
confidence: 99%
“…Similarly, the confederate controller also recommended that pilots should space on an aircraft that is two or three aircraft ahead of 4.D. [3][4][5][6][7][8][9][10][11] them, instead of the one directly in front of them. The controller noted that controllers find this strategy an effective way to buffer the effects of transient spacing variations of the few immediately leading aircraft on a trailing aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive simulation studies [6][7][8][9][10][11][12] have shown that interval managed CDAs is a viable concept that yields good spacing performance and throughput, considerable noise and fuel reduction, manageable pilot workload, and high pilot acceptance. A recent simulation has also been conducted to explore the effects of offnominal events introduced after the top of descent (TOD) [13].…”
Section: Introductionmentioning
confidence: 99%
“…CDA (see Figure 1) allows aircraft to approach moderately dense terminal areas, eliminating the level altitude segments and their associated thrust transients at low altitude, while flying efficient, near-idle descent trajectories that save fuel, and reduce emissions and noise (Ren et al, 2011;Weitz et al, 2005). However, these procedures are not in use everywhere because effective implementation may be difficult since aircraft require special equipment and can have a negative impact on the airspace throughput and controller workload (Jackson, 2009;Reynolds et al, 2005).…”
Section: Operational Procedures For Avoiding Aircraft Noisementioning
confidence: 99%